Capillary microsampling of 25 µl blood for the determination of toxicokinetic parameters in regulatory studies in animals. (March 2012) - Jonsson, Ove; Villar, Rodrigo Palma; Nilsson, Lars B; Norsten-Höög, Carina; Brogren, Jacob; Eriksson, Marie; Königsson, Kristian; Samuelsson, Anders
Background: Capillary microsampling (CMS) is a new technique for simplified collection, handling and analysis of small, exact volumes of liquid matrices. CMS was compared with conventional large volume sampling, in toxicology studies in rat and dog.Results: Bioanalytical validation data were well within acceptance limits. Toxicokinetic (TK) parameters from microsampling were in agreement with data from conventional volume sampling. Clinical pathology parameters in rats measured 2 days after repeated microsampling were not affected when compared with rats not sampled.Conclusion: The fast collection and simple handling of small, exact volumes of liquid blood makes the CMS technique generic and flexible, as well as easily implemented and automated. Presented data support that TK measurements can be performed in main study rats, instead of dosing additional satellite animals only for TK sampling, giving both a higher scientific value and a substantial reduction of animal numbers in preclinical development.